Cannabis Use in an English Community: Acceptance, Anxieties, and the Liminality of Drug Prohibition. (December 2018) - Taylor, Stuart; Beckett Wilson, Helen; Barrett, Giles; Jamieson, Janet; Grindrod, Lauren
Cannabis occupies an ambiguous social, cultural, economic, and legal position, meaning that the way communities construct, interact with, and interpret drug markets is a complicated and uncertain process. This article seeks to explain these ambiguities by investigating the place of cannabis use in a UK borough, drawing on qualitative empirical data collated from a sample ( N = 68) of practitioners, local residents, cannabis users, and their families. In doing so, the article employs the concept of liminality (whereby individuals and spaces occupy a position at both ends of a threshold) to explore how community behaviors and norms relate to issues of space, harm, and drug policy. The article contextualizes the position of cannabis use within the fieldwork site, exploring a series of competing contradictions that divided participants between the rhetoric and reality of drug prohibition. Drug prohibition suggests cannabis use to be dangerous, which prompted concern. However, the lived reality of prohibition for residents sat in stark juxtaposition: The drug was used commonly and publicly, was effectively decriminalized, and its use (reluctantly) accommodated. This malaise placed residents within what is described here as the liminality of drug prohibition, in which notions of the licit and illicit became blurred and whereby the illegality of cannabis augmented anxieties yet simultaneously proved a barrier to addressing them. In conclusion, the current study provides further evidence of prohibitionist drug policy proliferating rather than mitigating drug-related harms.